2021
DOI: 10.1007/s10072-021-05156-8
|View full text |Cite
|
Sign up to set email alerts
|

Static magnetic stimulation in the central nervous system: a systematic review

Abstract: Objective To systematically review the literature on the use of the transcranial static magnetic stimulation (tSMS) technique in humans and animals, its effects on different areas of the central nervous system (CNS), its influence on neural excitability and on the subject's behavior, and its biological effects and future possibilities. All static magnetic field applications that can be considered to have a physiologically similar effect have been reviewed. Methods We searched studies using key terms in NCBI Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
(217 reference statements)
0
1
0
Order By: Relevance
“…In the particular case of epilepsy, the results have been inconclusive probably due to the variability in the stimulation protocols and etiological heterogeneity (for a comprehensive review see 8 ). One of the most recently incorporated technique to the NIBS family is transcranial static magnetic stimulation (tSMS) 9 , whose application produces a clear and reproducible reduction of cortical excitability [10][11][12][13][14][15] . Following this line, in a recent paper we demonstrated that tSMS of moderate intensity (0.5 T) applied alone was able to delay and reduce the characteristic EEG signs of epileptiform discharges, both in rat and monkey 13 .…”
mentioning
confidence: 99%
“…In the particular case of epilepsy, the results have been inconclusive probably due to the variability in the stimulation protocols and etiological heterogeneity (for a comprehensive review see 8 ). One of the most recently incorporated technique to the NIBS family is transcranial static magnetic stimulation (tSMS) 9 , whose application produces a clear and reproducible reduction of cortical excitability [10][11][12][13][14][15] . Following this line, in a recent paper we demonstrated that tSMS of moderate intensity (0.5 T) applied alone was able to delay and reduce the characteristic EEG signs of epileptiform discharges, both in rat and monkey 13 .…”
mentioning
confidence: 99%